(untitled) (Economics and region, 2023)
Before ChatGPT was launched in November 2022, the development of AI-based chatbots was rather slow and lacked significant results. Their use was not as widespread as in 2023. The main users were mainly companies, in particular financial institutions, which used AI to collect and analyze various data necessary for the successful conduct of their activities, as well as to develop online chatbot-based consultants. Currently, AI is having a significant impact on all industries, including finance, expanding the capabilities of financial companies and improving the efficiency of their financial services. As a result of the rapid development of AI, the question arises as to how the use of AI-based chatbots can affect the work of people in the financial sector and the financial sector as a whole. Therefore, this study is relevant, as it is necessary to understand what artificial intelligence is capable of, what to expect from it, and whether it can change the way people work. This article presents a comprehensive study of AI-based chatbots and their potential in the financial sector. The article discusses in detail the possibilities of using chatbots to provide various types of financial services, including information, transactional, and advisory services. The author analyzes various types and functionalities of chatbots that are actively used in the financial sector, including informational chatbots that provide customers with up-to-date information on the financial market; transactional chatbots that allow customers to conduct various financial transactions; and consulting chatbots that provide useful advice and answers to customer questions. Special attention is paid to free chatbots based on artificial intelligence and their advantages and disadvantages. It is noted that training chatbots on the basis of their own generated data can lead to a "model collapse" that requires careful management. The article also discusses the main dangers associated with the use of AI-based chatbots in the financial sector and considers ways to avoid them. Based on the research findings, the article identifies trends in the development of chatbots in the financial services sector, such as improving customer experience, automating processes, reducing companies’ costs and increasing their revenues.